Pengembangan media pembelajaran quiz game untuk keterampilan membaca aksara jawa peserta didik kelas v sekolah dasar - Ilham Ariwijaya; Joko Daryanto; Dwi Yuniasih Saputri (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
The purpose of this study was to describing the development of quiz game learning media for Javanese script reading skills in fifth grade students of Mangkubumen Kidul elementary shool, Laweyan District, Surakarta. This research is a called RnD (research and development) and get to the stage of development. The research subjects were in fifth grade students of Mangkubumen Kidul elementary school, totaling 8 students. Sources of data come from students and teachers. Data collection techniques using interviews and document analysis. Validation techniques are carried out by material expert, media expert, and practitioner expert. The results of this product was in the good category with the precentage the material expert of 88,54%, the media expert of 98,75, and the practitioner expert of 85,22%. The process of creating learning media using Construct2 to build the program and Adobe Photoshop CS6 and CorelDRAW X5 to make a graphic design. The final result of this research is a product quiz game learning media for Javanese script reading skills that can be access on the device or smartphone.